High-torque EPDM synchronous belt and manufacturing process thereof
By adopting the design of a high-torque EPDM synchronous belt in the synchronous belt, using the combination of EPDM composite tooth glue layer and other materials, the problem of insufficient impact resistance of the toothed part of the synchronous belt is solved, and higher impact resistance and toughness are achieved.
Patent Information
- Application Number
- CN202411529057.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The teeth of the existing synchronization belt have little impact resistance, and it is easy to jump and knock out teeth when impacted, resulting in failure.
The design of high torque EPDM synchronization belt is adopted, including a powerful layer, an EPDM composite tooth glue layer, a cloth layer and a reinforcement layer arranged in sequence. The raw materials of the EPDM composite tooth glue layer are EPDM matrix, reinforcement filler, crosslinking agent, vulcanization additive, The combination of plasticizer, toughener and impact resistance is improved by combining these components.
It significantly improves the impact resistance of the toothed part of the synchronous belt, enhances its impact resistance and toughness, and extends the service life of the synchronous belt.
Smart Images

Figure HDA0005110024730000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of synchronous belts, and in particular to a high-torque EPDM synchronous belt and a manufacturing process thereof. Background Art
[0002] The synchronous belt is an annular belt with steel wire rope or glass fiber as the strong layer and rubber as the outer layer. The synchronous belt has the advantages of chain, gear and V-belt. The inner circumference of the synchronous belt is made into teeth to mesh with the toothed pulley. When rotating, the power is transmitted by the meshing of the belt teeth of the synchronous belt and the tooth grooves of the toothed pulley. The commonly used synchronous belt is basically made of neoprene with a hardness of 75±5 degrees. The impact resistance of the teeth is relatively low. When impacted, it is easy to jump teeth, causing the teeth to fall off and fail. Summary of the invention
[0003] In order to improve the impact resistance of the teeth of a synchronous belt, the present application provides a high-torque EPDM synchronous belt and a manufacturing process thereof.
[0004] In the first aspect, the present application provides a high torque EPDM synchronous belt, which adopts the following technical solution: A high-torque EPDM synchronous belt comprises a strength layer, an EPDM composite tooth rubber layer, a cloth layer and a reinforcement layer which are arranged in sequence; the raw materials of the EPDM composite tooth rubber layer comprise the following components in parts by weight: 55-65 parts of EPDM matrix, 15-25 parts of reinforcing filler, 1-5 parts of cross-linking agent, 1-3 parts of vulcanizing aid, 1-5 parts of plasticizer, 5-10 parts of toughening agent and 5-10 parts of impact resister.
[0005] By adopting the above technical scheme, the EPDM matrix can improve the hardness of the EPDM composite tooth rubber layer, the reinforcing filler can improve the mechanical properties and impact resistance of the EPDM composite tooth rubber layer, the plasticizer can improve the flexibility of the EPDM composite tooth rubber layer, and the toughening agent and impact resistant agent can be used to improve the toughness and impact resistance of the EPDM composite tooth rubber layer. Finally, a cloth layer and a reinforcing layer are compounded on the EPDM composite tooth rubber layer, thereby improving the impact resistance of the synchronous belt teeth.
[0006] In a specific embodiment, the method for preparing the reinforcing filler comprises the following steps: Stir γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; The carbon nanotubes and nano calcium carbonate are stirred and mixed evenly to obtain a mixture. During the stirring process, the spraying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain a reinforcing filler.
[0007] By adopting the above technical scheme, γ-aminopropyltriethoxysilane is first dissolved in ethanol, and then slowly sprayed while stirring the mixture. After spraying, stirring is continued and drying is performed to obtain a reinforcing filler with a good dispersion effect. The composite filler composed of carbon nanotubes and nano-calcium carbonate can further improve the mechanical properties and impact resistance of the EPDM composite tooth rubber layer; in addition, the γ-aminopropyltriethoxysilane on the surface of the reinforcing filler can further improve the crosslinking strength of the EPDM composite tooth rubber layer.
[0008] In a specific embodiment, the weight ratio of the spraying liquid to the mixed material is 1:(13-14).
[0009] By adopting the above technical solution, the ratio of the spraying liquid to the mixed material is further limited, and the modification effect on the carbon nanotubes and nano calcium carbonate is improved.
[0010] In a specific embodiment, the crosslinking agent includes one or more of dicumyl peroxide, bis(tert-butylperoxy)decane, and diacetyl peroxide.
[0011] By adopting the above technical scheme, dicumyl peroxide, di(tert-butylperoxy)decane and diacetyl peroxide all have good cross-linking effects, among which dicumyl peroxide produces free radicals by decomposing at high temperature, thereby promoting the cross-linking reaction between EPDM molecular chains to achieve a better cross-linking effect.
[0012] In a specific embodiment, the vulcanization aid includes a mixture of sulfur and a ZDEC accelerator.
[0013] By adopting the above technical solution and using the composite vulcanization aid composed of sulfur and ZDEC accelerator, the EPDM composite rubber can be prompted to form a three-dimensional spatial network structure, thereby improving the strength of the EPDM composite tooth rubber layer.
[0014] In a specific embodiment, the plasticizer includes dioctyl phthalate.
[0015] By adopting the above technical solution, dioctyl phthalate has low volatility and good solubility, and can play a good softening role without significantly affecting other physical properties.
[0016] In a specific embodiment, the toughening agent includes one of styrene-ethylene-butylene-styrene copolymer and polyolefin elastomer.
[0017] In a specific embodiment, the impact resistant agent includes a mixture of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide.
[0018] By adopting the above technical scheme, the butyl acrylate copolymer and the polyester polyurethane elastomer work synergistically to significantly enhance the toughness of the material; maleic anhydride grafted polypropylene improves the compatibility between the components and makes the mixing more uniform; fatty acid amide ensures the uniform distribution of the components in the final product and improves the impact resistance of the EPDM composite tooth rubber layer.
[0019] In a specific embodiment, the reinforcing layer is made of ultra-high molecular weight polyethylene or polytetrafluoroethylene, and has a thickness of 0.1-0.5 mm.
[0020] In the second aspect, the present application provides a manufacturing process for a high torque EPDM synchronous belt, which adopts the following technical solution: A manufacturing process of a high torque EPDM synchronous belt comprises the following steps: Mixing: Mixing the EPDM matrix, reinforcing filler, cross-linking agent, vulcanizing aid, plasticizer, toughening agent and impact resistant agent to obtain a mixed rubber; Calendering: Calendering the mixed rubber on the strong layer to form a rubber layer, and then grinding, cutting and slotting the rubber layer to obtain an EPDM composite tooth rubber layer; Compounding: First compound the cloth layer on the EPDM composite tooth rubber layer, and then compound the reinforcement layer on the cloth layer to obtain a high torque EPDM synchronous belt.
[0021] By adopting the above technical scheme, the EPDM matrix, reinforcing filler, cross-linking agent, vulcanizing agent, plasticizer, toughening agent and impact resister are firstly mixed to obtain a mixed rubber, which is then calendered on the strength layer to form a rubber layer, which is then polished, cut and grooved to obtain an EPDM composite tooth rubber layer, and finally the upper cloth layer and the reinforcement layer are compounded to obtain a high-torque EPDM synchronous belt with good impact resistance.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, the EPDM matrix can improve the hardness of the EPDM composite tooth rubber layer, the reinforcing filler can improve the mechanical properties and impact resistance of the EPDM composite tooth rubber layer, the plasticizer can improve the flexibility of the EPDM composite tooth rubber layer, and the toughening agent and impact resistance agent can be used to improve the toughness and impact resistance of the EPDM composite tooth rubber layer. Finally, a cloth layer and a reinforcing layer are compounded on the EPDM composite tooth rubber layer, thereby improving the impact resistance of the tooth portion of the synchronous belt; 2. The butyl acrylate copolymer and polyester polyurethane elastomer in the impact resister of the present application work synergistically with each other to significantly enhance the toughness of the material; maleic anhydride grafted polypropylene improves the compatibility between the components and makes the mixing more uniform; fatty acid amide ensures the uniform distribution of the components in the final product and improves the impact resistance of the EPDM composite tooth rubber layer; 3. The method of the present application first mixes the EPDM matrix, reinforcing filler, crosslinking agent, vulcanization aid, plasticizer, toughening agent and impact resister to obtain a mixed rubber, which is then calendered on the strength layer to form a rubber layer, which is then polished, cut and grooved to obtain an EPDM composite tooth rubber layer, and finally a cloth layer and a reinforcement layer are compounded to obtain a high-torque EPDM synchronous belt with good impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a cross-sectional schematic diagram used to embody the high-torque EPDM synchronous belt in Example 1 of the present application.
[0024] Explanation of reference numerals: 1. Strong layer; 2. EPDM composite tooth rubber layer; 3. Cloth layer; 4. Reinforcement layer. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] All raw materials in the examples can be obtained commercially. The crosslinking agent includes but is not limited to a mixture of one or more of dicumyl peroxide, di(tert-butylperoxy)decane, and diacetyl peroxide, and dicumyl peroxide is preferred in the present application; the toughening agent includes but is not limited to one of styrene-ethylene-butylene-styrene copolymer and polyolefin elastomer, and is not limited to styrene-ethylene-butylene-styrene copolymer.
[0027] Preparation Example Preparation Example 1 Preparation Example 1 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes and nano-calcium carbonate into a high-speed mixer and stir to obtain a mixture. During the stirring process, slowly spray the spray liquid into the mixture. After the spraying is completed, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the mixture is 1:12.5.
[0028] Preparation Example 2 Preparation Example 2 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes and nano-calcium carbonate into a high-speed mixer and stir to obtain a mixture. During the stirring process, slowly spray the spray liquid into the mixture. After the spraying is completed, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the mixture is 1:13.
[0029] Preparation Example 3 Preparation Example 3 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes and nano-calcium carbonate into a high-speed mixer and stir to obtain a mixture. During the stirring process, slowly spray the spray liquid into the mixture. After the spraying is completed, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the mixture is 1:13.5.
[0030] Preparation Example 4 Preparation Example 4 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes and nano-calcium carbonate into a high-speed mixer and stir to obtain a mixture. During the stirring process, slowly spray the spray liquid into the mixture. After the spraying is completed, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the mixture is 1:14.
[0031] Preparation Example 5 Preparation Example 5 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes and nano-calcium carbonate into a high-speed mixer and stir to obtain a mixture. During the stirring process, slowly spray the spray liquid into the mixture. After the spraying is completed, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the mixture is 1:14.5.
[0032] Preparation Example 6 Preparation Example 6 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add carbon nanotubes into a high-speed mixer, and slowly spray the spray liquid into the carbon nanotubes during stirring. After spraying, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforced filler; wherein the weight ratio of the spray liquid to the carbon nanotubes is 1:13.5.
[0033] Preparation Example 7 Preparation Example 7 provides a method for preparing a reinforcing filler, comprising the following steps: Stirring γ-aminopropyltriethoxysilane, ethanol and water evenly to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Add nano calcium carbonate into a high-speed mixer, and slowly spray the spray liquid into the nano calcium carbonate during stirring. After spraying, continue stirring for 0.5 hours, and then dry at 100°C for 1.5 hours to obtain a reinforcing filler; wherein the weight ratio of the spray liquid to the nano calcium carbonate is 1:13.5. Example
[0034] Example 1 Embodiment 1 provides a high torque EPDM synchronous belt.
[0035] Reference Figure 1 A high torque EPDM synchronous belt comprises a strength layer 1, an EPDM composite tooth rubber layer 2, a cloth layer 3, and a reinforcement layer 4 which are arranged in sequence.
[0036] Embodiment 1 also provides a process for manufacturing a high torque EPDM synchronous belt, comprising the following steps: Mixing: 55kg EPDM matrix, 15kg reinforcing filler in Preparation Example 1, 1kg cross-linking agent, 1kg vulcanization aid, 1kg plasticizer, 5kg toughening agent, and 5kg impact agent are mixed to obtain a mixed rubber; wherein the cross-linking agent is dicumyl peroxide; the vulcanization aid is a mixture of sulfur and ZDEC accelerator, and the weight ratio of sulfur to ZDEC accelerator is 2:1; the plasticizer is dioctyl phthalate; the toughening agent is styrene-ethylene-butylene-styrene copolymer; the impact agent is a mixture of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide stirred at 90°C for 1.5h, the stirring speed is 1500rpm, and the weight ratio of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide is 25:15:7.5:3.5; Calendering: Calendering the mixed rubber on the strong layer 1 to form a rubber layer, and then grinding, cutting and slotting the rubber layer to obtain the EPDM composite tooth rubber layer 2; wherein the strong layer 1 is made of wire rope; Composite: The cloth layer 3 is first composited on the EPDM composite tooth rubber layer 2, and then the reinforcing layer 4 is composited on the cloth layer 3 to obtain a high torque EPDM synchronous belt; wherein the cloth layer 3 is a nylon elastic cloth layer; the reinforcing layer 4 is a polytetrafluoroethylene layer with a thickness of 0.3 mm.
[0037] Example 2 The difference between Example 2 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 2, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0038] Example 3 The difference between Example 3 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 3, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0039] Example 4 The difference between Example 4 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 4, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0040] Example 5 The difference between Example 5 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 5, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0041] Example 6 The difference between Example 6 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 6, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0042] Example 7 The difference between Example 7 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 7, 1 kg of cross-linking agent, 1 kg of vulcanizing aid, 1 kg of plasticizer, 5 kg of toughening agent, and 5 kg of impact agent are mixed to obtain a mixed rubber; the remaining steps are consistent with Example 1.
[0043] Example 8 The difference between Example 8 and Example 3 is that the vulcanization aid is sulfur; the remaining steps are consistent with Example 3.
[0044] Example 9 The difference between Example 9 and Example 3 is that the impact-resistant agent is acrylic acid-butyl acrylate copolymer; the remaining steps are consistent with Example 3.
[0045] Example 10 The difference between Example 10 and Example 3 is that the impact-resistant agent is a polyester polyurethane elastomer; the remaining steps are consistent with Example 3.
[0046] Comparative Example Comparative Example 1 Comparative Example 1 provides a manufacturing process for a synchronous belt, comprising the following steps: Mixing: 55kg of chloroprene rubber, 1kg of crosslinking agent, 1kg of vulcanizing aid, 1kg of plasticizer, and 5kg of toughening agent are mixed to obtain a mixed rubber; wherein the crosslinking agent is dicumyl peroxide; the vulcanizing aid is a mixture of sulfur and ZDEC accelerator, and the weight ratio of sulfur to ZDEC accelerator is 2:1; the plasticizer is dioctyl phthalate; and the toughening agent is styrene-ethylene-butylene-styrene copolymer; Calendering: Calender the mixed rubber on the strong layer to form a rubber layer, which is then polished, cut and grooved to obtain a synchronous belt; the strong layer is made of wire rope.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that, mixing: 55kg EPDM matrix, 1kg cross-linking agent, 1kg vulcanization aid, 1kg plasticizer, 5kg toughening agent, and 5kg impact agent are mixed to obtain a mixed rubber; wherein the cross-linking agent is diisopropylbenzene peroxide; the vulcanization aid is a mixture of sulfur and ZDEC accelerator, and the weight ratio of sulfur to ZDEC accelerator is 2:1; the plasticizer is dioctyl phthalate; the toughening agent is styrene-ethylene-butylene-styrene copolymer; the impact agent is a mixture of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide stirred at 90°C for 1.5h, the stirring speed is 1500rpm, and the weight ratio of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide is 25:15:7.5:3.5; the remaining steps are consistent with Example 1.
[0048] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that, in the mixing, 55 kg of EPDM matrix, 15 kg of reinforcing filler in Preparation Example 1, 1 kg of cross-linking agent, 1 kg of vulcanization aid, 1 kg of plasticizer, and 5 kg of toughening agent are mixed to obtain a mixed rubber; wherein the cross-linking agent is diisopropylbenzene peroxide; the vulcanization aid is a mixture of sulfur and ZDEC accelerator, and the weight ratio of sulfur to ZDEC accelerator is 2:1; the plasticizer is dioctyl phthalate; the toughening agent is styrene-ethylene-butylene-styrene copolymer; and the remaining steps are consistent with Example 1.
[0049] Performance testing Impact resistance: The impact resistance of the teeth on the synchronous belt in each embodiment and comparative example was tested. The higher the impact resistance, the better the impact resistance of the teeth on the synchronous belt.
[0050] Table 1 Performance test results of synchronous belt sample <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 43.7 Example 2 47.5 Example 3 47.7 Example 4 47.7 Example 5 44.2 Example 6 46.5 Example 7 46.7 Example 8 47.0 Example 9 46.1 Example 10 46.3 Comparative Example 1 32.2 Comparative Example 2 40.2 Comparative Example 3 41.3 In combination with Example 1 and Comparative Examples 1-3, the impact resistance of the synchronous belt teeth in Example 1 is the best. It can be seen that by using the synchronous belt in the present application, the EPDM matrix can improve the hardness of the EPDM composite tooth rubber layer 2, the reinforcing filler can improve the mechanical properties and impact resistance of the EPDM composite tooth rubber layer 2, the plasticizer can improve the flexibility of the EPDM composite tooth rubber layer 2, and the toughening agent and impact resister can be used to improve the toughness and impact resistance of the EPDM composite tooth rubber layer 2. Finally, the cloth layer 3 and the reinforcement layer 4 are compounded on the EPDM composite tooth rubber layer 2, thereby improving the impact resistance of the synchronous belt teeth.
[0051] Combined with Examples 1-5, the impact resistance of the synchronous belt teeth in Examples 2-4 is better. It can be seen that when preparing the reinforcing filler, the ratio of the spraying liquid to the mixed material is preferably 1: (13-14), and the performance of the obtained reinforcing filler is better.
[0052] Combining Example 3, Example 6 and Example 7, the impact resistance of the synchronous belt teeth in Example 3 is the best. It can be seen that when preparing the reinforcing filler, the filler is a mixture of carbon nanotubes and nano-calcium carbonate, and the performance of the reinforcing filler is better.
[0053] Combining Example 3 and Example 8, the impact resistance of the teeth of the synchronous belt in Example 3 is better. It can be seen that when mixing and making rubber, the vulcanization aid is preferably a mixture of sulfur and ZDEC accelerator, and the performance of the synchronous belt is better.
[0054] In combination with Example 3, Example 9 and Example 10, the impact resistance of the synchronous belt tooth portion in Example 3 is the best. It can be seen that when mixing and making rubber, the impact resistance agent is preferably a mixture of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene, and fatty acid amide. The acrylic acid butyl acrylate copolymer and the polyester polyurethane elastomer work synergistically to significantly enhance the toughness of the material; maleic anhydride grafted polypropylene improves the compatibility between the components and makes the mixing more uniform; fatty acid amide ensures that the components in the final product are evenly distributed, thereby improving the impact resistance of the final synchronous belt tooth portion.
[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high torque EPDM synchronous belt, characterized by: It comprises a strength layer (1), an EPDM composite tooth rubber layer (2), a cloth layer (3), and a reinforcement layer (4) which are arranged in sequence; the raw materials of the EPDM composite tooth rubber layer (2) comprise the following components in parts by weight: 55-65 parts of EPDM matrix, 15-25 parts of reinforcing filler, 1-5 parts of cross-linking agent, 1-3 parts of vulcanizing aid, 1-5 parts of plasticizer, 5-10 parts of toughening agent, and 5-10 parts of impact resistance agent.
2. A high torque EPDM synchronous belt according to claim 1, characterized in that: The preparation method of the reinforcing filler comprises the following steps: Stir γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; The carbon nanotubes and nano calcium carbonate are stirred and mixed evenly to obtain a mixture. During the stirring process, the spraying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain a reinforcing filler.
3. A high torque EPDM synchronous belt according to claim 2, characterized in that: The weight ratio of the spraying liquid to the mixed material is 1:(13-14).
4. A high torque EPDM synchronous belt according to claim 1, characterized in that: The cross-linking agent includes one or more of dicumyl peroxide, bis(tert-butylperoxy)decane, and diacetyl peroxide.
5. The high torque EPDM synchronous belt according to claim 1, characterized in that: The vulcanization aid comprises a mixture of sulfur and a ZDEC accelerator.
6. A high torque EPDM synchronous belt according to claim 1, characterized in that: The plasticizer includes dioctyl phthalate.
7. The high torque EPDM synchronous belt according to claim 1, characterized in that: The toughening agent includes one of styrene-ethylene-butylene-styrene copolymer and polyolefin elastomer.
8. The high torque EPDM synchronous belt according to claim 1, characterized in that: The impact-resistant agent comprises a mixture of acrylic acid butyl acrylate copolymer, polyester polyurethane elastomer, maleic anhydride grafted polypropylene and fatty acid amide.
9. The high torque EPDM synchronous belt according to claim 1, characterized in that: The reinforcing layer is made of ultra-high molecular weight polyethylene or polytetrafluoroethylene, and has a thickness of 0.1-0.5 mm.
10. A process for manufacturing a high torque EPDM synchronous belt according to any one of claims 1 to 9, characterized in that: The following steps are involved: Mixing: Mixing the EPDM matrix, reinforcing filler, cross-linking agent, vulcanizing aid, plasticizer, toughening agent and impact resistant agent to obtain a mixed rubber; Calendering: Calendering the mixed rubber on the strength layer (1) to form a rubber layer, and then grinding, cutting and slotting the rubber layer to obtain an EPDM composite tooth rubber layer (2); Compounding: Firstly compounding the cloth layer (3) on the EPDM compound tooth rubber layer (2), and then compounding the reinforcement layer (4) on the cloth layer (3), so as to obtain a high torque EPDM synchronous belt.